2021
DOI: 10.1186/s13104-021-05836-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydroxyethylstarch (HES 130/0.4) and 5% human albumin for volume substitution in pediatric neurosurgery: A retrospective, single center study

Abstract: Objective Colloid solutions are commonly used to maintain perioperative fluid homeostasis. In regard to perioperative infant-centered care, data about the impact of colloids are rare. New data suggest a possible positive effect of hydroxyethyl starch (HES) concerning blood brain barrier. Therefore we conduct a retrospective single center study of children scheduled for neurosurgery, age < five with a blood loss > 10% of body blood volume, receiving either 6% HES 130/0.4 or 5% human albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The HA group however showed a shorter ventilation time and length of hospital stay. The study is too weak, however, to show significant evidence in the safe use of colloids 23 .…”
Section: Colloidsmentioning
confidence: 84%
See 1 more Smart Citation
“…The HA group however showed a shorter ventilation time and length of hospital stay. The study is too weak, however, to show significant evidence in the safe use of colloids 23 .…”
Section: Colloidsmentioning
confidence: 84%
“…Schick et al ( 2021), compared the use of HES (130/0,4) and HA in neurosurgery with major blood loss 23 . They found that the HA infusion volumes were substantially greater, and a more positive fluid balance was seen post-surgery in the HA group.…”
Section: Colloidsmentioning
confidence: 99%